2022
DOI: 10.1093/femsec/fiac123
|View full text |Cite
|
Sign up to set email alerts
|

Microbial ecology of the Southern Ocean

Abstract: The Southern Ocean (SO) distributes climate signals and nutrients worldwide, playing a pivotal role in global carbon sequestration. Microbial communities are essential mediators of primary productivity and carbon sequestration, yet we lack a comprehensive understanding of microbial diversity and functionality in the SO. Here, we examine contemporary studies in this unique polar system, focusing on prokaryotic communities and their relationships with other trophic levels (i.e. phytoplankton and viruses). Strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 198 publications
1
4
0
Order By: Relevance
“…Hence, it is possible to observe marine taxa with known global distribution, such as SAR11, Flavobacteriales and Rhodobacterales [ 21 , 25 ]. Consistent with the literature, the Southern Ocean is an isolated region where the conditions shape bacterioplankton communities differently from other oceanic regions (including the Arctic Ocean), as well as driven by seasonal eukaryotic phytoplankton blooms, which boost primary production in this oceanic region [ 72 ]. All of the above give rise to unique cellular OTUs [ 21 ], as also observed in the mobilome revealed by this study.…”
Section: Discussionsupporting
confidence: 55%
“…Hence, it is possible to observe marine taxa with known global distribution, such as SAR11, Flavobacteriales and Rhodobacterales [ 21 , 25 ]. Consistent with the literature, the Southern Ocean is an isolated region where the conditions shape bacterioplankton communities differently from other oceanic regions (including the Arctic Ocean), as well as driven by seasonal eukaryotic phytoplankton blooms, which boost primary production in this oceanic region [ 72 ]. All of the above give rise to unique cellular OTUs [ 21 ], as also observed in the mobilome revealed by this study.…”
Section: Discussionsupporting
confidence: 55%
“…Despite the importance of the SIO in modulating global climate and heat uptake in the ocean [ 1 , 42 , 98 ], we lack taxonomic insights regarding the functional roles of viruses. Using two of the most widely used pipelines [ 54 , 99 ], we explored viral communities in deep SIO waters.…”
Section: Resultsmentioning
confidence: 99%
“…Disentangling the phylogenetically diverse assemblages of bacteria, fungi, phytoplankton, and viruses and their contributions to ecosystem services in the global ocean remains a major endeavour. There is strong evidence that these assemblages influence the biological carbon pump in marine environments [ 1 , 2 ]. Among these assemblages, viruses are the most numerically abundant [ 3 ], and recent evidence has demonstrated their profound influence on prokaryotic lifestyles in the oceans [ 4–8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have provided insights into the species‐specific temperature responses of cultured isolates and have identified many psychrophilic specialists able to optimize their metabolism and cellular features to enable life at extremely low temperature (D'Amico et al, 2006). However, culture‐independent approaches have demonstrated that in addition to endemic specialists, many cosmopolitan bacterial taxa sufficiently tolerate the Antarctic marine environment (Castillo et al, 2022; Delmont et al, 2014; Liu et al, 2020; Luria et al, 2017; Piontek et al, 2022). Recent studies using high‐throughput sequencing technologies identified key taxa in bacterial communities of Antarctic marginal seas that were mainly assigned to genera of the orders Flavobacteriales , Chitinophagales (both Bacteroidia ), Rhodobacterales ( Alphaproteobacteria ), Cellvibrionales and Pseudomonadales (both Gammaproteobacteria ) (Delmont et al, 2014; Grzymski et al, 2012; Luria et al, 2016; Piontek et al, 2022).…”
Section: Introductionmentioning
confidence: 99%